Breeding Novel Rice Hybrids for Aerobic Ecology: A Way Out from Global Warming and Water Crisis - Ambati Srijan; Ponnuvel Senguttuvel; Kuldeep Singh Dangi; Sagi Sudheer Kumar; Raman Meenakshi Sundaram; Darshanoju Srinivasa Chary (Agronomy, 2023)
The development of novel rice hybrids is a prospectus area of research for enhancing grain yield to meet the growing population demands. An experiment was conducted in 2016–2017 to develop novel rice hybrids for aerobic ecology with lesser yield penalties than irrigated ecosystems, with the added advantage of reduced methane emissions and water budget as witnessed in irrigated systems. Based on the restorer-maintainer reaction and spikelet fertility (%), ten restorer lines were selected to cross with three CMS (Cytoplasmic male sterile) lines in the Line by Tester fashion in Yasangi (summer) season 2016–2017. They resulted in 30 experimental hybrids besides 13 parental lines (10 restorer lines and 3 B—lines of akin CMS lines) and checks (GK 5022, CR Dhan 201) assessed during the Vankalam (rainy) season 2017 at three different places/locations viz., Rajendranagar, Warangal, and Kampasagar. The outcome of the experiment was that two experimental hybrids viz., APMS-6A × HRSV-7 and IR-79156A × ATR-372, were categorized as stable hybrids with desirable sca (Specific combining ability) effects, heterosis (ranging from 7% to 13%) over best check GK 5022, along with an in-essence performance for yield and other yield attributing characters.